Analyzing and Improving the Performance of Flexible Manufacturing Systems (The International Journal of Engineering & Information Technology (IJEIT), 2025)
With the intense competition in the market, manufacturing managers are trying to optimize production times, improve product quality, increase product variety, and reduce production costs. Therefore, in the current market environment, these manufacturing environments must be designed, analyzed, and improved based on market challenges in order to survive and thrive in the industry. This paper presents a case study of a linear pallet system for moving parts on pallets in a flexible manufacturing system (FMS) shop. The objective of this study is to analyze the performance of the FMS and propose ways to improve its performance. To determine the current productivity and utilization of work space on the current FMS shop, the Bottleneck Model analysis method and its extension "Extended Bottleneck Model" are used. The proposed FMS that standardizes operations across workstations shows significant improvement in workstation utilization and production throughput.